The Galileo affair : a documentary history - Finocchiaro, Maurice A., 1942-; Galilei, Galileo, 1564-1642.; Galilei, Galileo, 1564-1642. (Berkeley : University of California, 1989)
"A classic introduction to Galileo's masterpiece."--William A. Wallace, author of Galileo's Logic of Discovery and Proof."--
Documents. I. Correspondence (1613-1615) ; II. Galileo's considerations on the Copernican opinion (1615) ; III. Galileo's letter to the Grand Duchess Christina (1615) ; IV. Galileo's discourse on the tides (1616) ; V. The earlier Inquisition proceedings (1615-1616) ; VI. Galileo's reply to Ingoli (1624) ; VII. Miscellaneous documents (1618-1633) ; VIII. Diplomatic correspondence (1632-1633) ; IX. The later Inquisition proceedings (1633) -- Appendixes. Chronology of events ; Concordance to the documents ; Biographical glossary.
Includes bibliographical references (pages 365-373) and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Galilei, Galileo, -- 1564-1642.; Galilei, Galileo, -- 1564-1642; Religion and science -- History; Inquisition; Religion et sciences -- Histoire; Inquisition; TECHNOLOGY & ENGINEERING -- Mechanical; SCIENCE -- General; Inquisition; Religion and science; History